Analisis Pengungkapan Environmental, Social, dan Governance terhadap Kinerja Keuangan - Najla Huwaida; Akhmad Saebani; Ronny Andesto (Jurnal Ragam Pengabdian, 2026)
This study empirically analyzes the impact of environmental, social, and governance (ESG) disclosures on financial performance. The sample consists of 77 manufacturing companies, including 46 from Indonesia, 15 from Malaysia, and 16 from Thailand, listed on the Indonesia Stock Exchange (IDX), Bursa Malaysia, and the Stock Exchange of Thailand (SET), with 231 observations over the 2022–2024 period. Samples were selected using purposive sampling. Panel data regression was employed using STATA 17 at a 5% significance level, with model selection determined through Chow, Lagrange Multiplier, and Hausman tests. The results indicate that environmental disclosure has a positive and significant effect on financial performance, as companies with greater environmental transparency tend to gain investor trust and improve operational efficiency. However, social and governance disclosures do not significantly influence financial performance, suggesting that social initiatives require substantial upfront costs with long-term benefits, while governance practices often remain formal compliance without substantive implementation. These findings support the stakeholder theory perspective that environmental transparency enhances corporate legitimacy and financial outcomes.